A balanced cross-section through the eastern Nepal Siwalik hills, Bagmati river region, implications for the structure of the southern Himalaya (Journal of Nepal Geological Society, 1992)
A balanced cross-section has been constructed across the eastern Nepal Siwalik Hills along the Bagmati River in order to determine the structural geometry of the Himalayan foreland fold- thrust belt and to estimate tectonic shortening. The Siwalik Hills are underlain by a basal detachment, the Main Detachment Fault, at a depth of about 6.9km to 8km. The Main Boundary Thrust, the Chaura- Marin Thrust and the Main Frontal Thrust are splay thrusts off the Main Detachment Fault which ramp directly up-section to the surface through 6.8 to 7.7km of Siwalik Sediments with no major intervening thrust flats; the Sub-Himalayan foreland fold thrust belt displays an emergent imbricate- fan geometry. Shortening across the Bagmati section of the Siwalik Hills has been 20km, or 40%, while thrusting along the Main Boundary Thrust has resulted in a minimum of another 25km of shortening.